PECULIARITIES OF THE INTERPRETATION OF NATIONAL FREEDOM IN THE PUBLICITATIONS OF IVAN BAHRIANYI AND GEORGE ORWELL: COMPARATIVE ASPECTS - Kobuta, S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article dwells on the peculiarities of the authors’ understanding of the national liberty in the definite historical circumstances. It compares the authors’ attitude towards the rights of the dependent nations to fight for their freedom. It observes the characteristics of the democratic world reaction on the liberation processes in the USSR done by George Orwell and Ivan Bahrjanyj. The emphasis is made on the peculiarities of the national liberty realization in the totalitarian regime and on the problem of the national identity preservation in the totalitarian state. A special attention is paid to the connection of the notions “free person” and “national liberty” and to the conditions of its realization. Similarities and differences in the George Orwell and Ivan Bahrjanyj interpretation of the national liberty and its limitation factors are defined.